Penguatan Pendidikan Karakter di Madrasah Aliyah Negeri 1 Ponorogo - Aunillah, Mahila Tahta; Handayani, Mia Baitul; Makhrus, Muhammad Labibullah (Yayasan Al-Aziziyah Tlogoagung Kedungadem Bojonegoro, 2023)
This research aimed to describe the Strategic Steps of Madrasah Aliyah Negeri 1 Ponorogo in Strengthening Character Education and to find out how big the school's priority is in efforts to strengthen character education for its students. The method that used in this research is descriptive method, with a qualitative approach. Data collection techniques using interview and observation techniques. This research resulted in findings; there is a Project to Strengthen the Pancasila Student Profile which is one of the policies in the Independent Curriculum. The Pancasila Student Profile places more emphasis on strengthening the national character of students. Then MAN 1 Ponorogo held a point application followed by punishment and rewards for students who violated the rules and students who excel with the indicators set by the school. The application of points with reward and punishment is considered effective in efforts to strengthen student character education, in addition to facilitating monitoring as well so that students are motivated to become students who are disciplined and achievers.